National products, the grand theories - Noviardi (Fakultas Ilmu Pendidikan UNP)
Persuading society to increase national productions is not just an easy evergreen concept. Million of rupiahs spent on advertisement, would not be enough to change society perceptions that imported products are better, which will result in decreasing interest for national productions. Researcher assumes there is a low interest to discuss national productions in qualitative research. Having this assumption as the background, researcher will explain the result of related literatures study about increase in national productions. The results will be discussed by using the theory of qualitative research, by combining several related theory into some grand theories.